(untitled) (Journal of Geography and Environmental Management, 2026)
For such a vast landlocked country as Kazakhstan, railway infrastructure is the main pillar of access to national and regional markets. In recent years, within the framework of the Nurly Zhol state program and international initiatives (CAREC, Middle Corridor), major projects aimed at modernizing the railway network and increasing its capacity have been implemented. However, a significant part of the length of the railway network, which is about 16 thousand km, is worn out (50-60% of the infrastructure is morally and physically outdated), and the share of electrified roads remains about 40%. The purpose of the article is to assess the trends in the modernization of railway infrastructure in Kazakhstan from a spatial economic and geographical point of view and analyze the impact of this modernization on access to regional and foreign markets. As materials of the study, open statistical data of the Kazakhstan railway (KTZ), data on railway cargo turnover of the World Bank, assessment reports of CAREC and ADB on the railway sector, as well as information and scientific publications on the documents of the Nurly Zhol program and infrastructure projects of recent years were used. The theory of spatial accessibility, economic and geographical probability indices, analysis of the structure of cargo flows along railway and transit corridors, typologization of regions by access to markets, as well as cartographic and comparative-statistical methods were used as a methodological basis. The integral accessibility index based on time and cost to international and domestic markets (Astana, Almaty, large industrial centers, Chinese border crossings, seaports) was calculated, and spatial differences between regions and railway junctions were assessed. The results of the study provide recommendations aimed at identifying priorities for the modernization of railway infrastructure, eliminating bottlenecks, clarifying the importance of integrated coordination with logistics hubs and digital technologies (digital Railways, Predictive Services, Smart Logistics).